2011
DOI: 10.3324/haematol.2010.036053
|View full text |Cite
|
Sign up to set email alerts
|

New insights into childhood autoimmune hemolytic anemia: a French national observational study of 265 children

Abstract: Since 2004, a national observational study has been aiming to thoroughly describe cases and identify prognostic factors. Patients from all French hematologic pediatric units have been included if they had a hemoglobin concentration less than 11 g/dL, a positive direct antiglobulin test and hemolysis. Evans' syndrome was defined by the association of autoimmune hemolytic anemia and immunological thrombocytopenic purpura. Data from patients' medical records were registered from birth to last follow-up. Autoimmun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
180
4
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(223 citation statements)
references
References 46 publications
11
180
4
4
Order By: Relevance
“…In a study by Aladjidi et al, (5) in which 265 children with AIHA were evaluated retrospectively, it was shown that 37% of patients had primary AIHA, 63% had secondary AIHA, previous infection was present in 10% of the cases of secondary AIHA, and immunologic causes were present in 53%. It has been shown that immunologic diseases develop subsequently in approximately half of patients who report infection initially and these patients show a chronic prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Aladjidi et al, (5) in which 265 children with AIHA were evaluated retrospectively, it was shown that 37% of patients had primary AIHA, 63% had secondary AIHA, previous infection was present in 10% of the cases of secondary AIHA, and immunologic causes were present in 53%. It has been shown that immunologic diseases develop subsequently in approximately half of patients who report infection initially and these patients show a chronic prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…These serological tests are considered important to exclude AIHA secondary to these infections. 2 AIHA secondary to infections was considered less likely in this patient due to compatible clinical picture and recurrent acute hemolysis. 2 There was unusual Þ nding of Vitamin B12 deÞ ciency in our patient.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…2 AIHA secondary to infections was considered less likely in this patient due to compatible clinical picture and recurrent acute hemolysis. 2 There was unusual Þ nding of Vitamin B12 deÞ ciency in our patient. Despite treatment with Vitamin B12, there was no clinical improvement and only after initiation of oral prednisolone, hemolytic activity was reduced thus obviating need for further transfusions.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations